Features of voice transmission in the LTE network - Khrystyuk, Andriy; Malanchuk, Yevheniy (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The main results of the research of methods of voice transmission in the fourth generation networks, the analysis of existing problems in voice transmission technologies, and also verification of quality and reliability of VoLTE technology in the laboratory environment are presented. Recommendations on the application of voice technology in LTE networks deployed in Ukraine, assessment of existing technologies used for transmitting voice over the fourth generation networks, and the creation of a test strategy for checking the reliability of voice transmission on the LTE network are presented